Feartures of recreational potential of forest ecosystems of Klinsko-Dmitrovskay Gryada - S N Volkov; A I Samodurov (RUDN Journal of Agronomy and Animal Industries, 2012)
The article is devoted to recreational opportunities of forest ecosystems of Clinsko-Dmytrovskaja Grjada. Recreational potential in connection of forest types was given as result of male study. As a result of studies is assessed the recreational potential in relation to forest types. The impact of various forms of rechation on the state of the main elements of the forest has been given. The description of flora and fauna have been given.